Thermophilic Geobacillus WSUCF1 Secretome for Saccharification of Ammonia Fiber Expansion and Extractive Ammonia Pretreated Corn Stover - Bhalla, Aditya; Arce, Jessie; Ubanwa, Bryan; Singh, Gursharan; Sani, Rajesh K.; Balan, Venkatesh (Frontiers in Microbiology, 2022)
A thermophilic Geobacillus bacterial strain WSUCF1 contains different Carbohydrate-Active Enzymes (CAZymes) capable of hydrolyzing hemicellulose in lignocellulosic biomass. Using proteomic, genomic, and bioinformatic tools, bioinformatics tools and genomic data were used to analyze the relative abundance of cellulolytic, hemicellulolytic, and lignin modifying enzymes present in the secretomes. Results showed that CAZyme profiles of secretome varied based on substrate type and complexity, composition, and pretreatment conditions. The enzyme activity of secretome also changed depending on the substrate used. The secretome were used in combination with commercial and purified enzymes to carry out saccharification of Ammonia Fiber Expansion pretreated corn stover and Extractive ammonia pretreated corn stover. When WSUCF1 bacterial secretome produced at different conditions was combined with a small percentage of commercial enzymes, we observed efficient saccharification of EA-CS, and the results were comparable to using a commercial enzyme cocktail (87% glucan and 70% xylan conversion). It also opens up the possibility of producing CAZymes in a biorefinery using inexpensive substrates such as Ammonia Fiber Expansion pretreated corn stover and avicel and eliminates expensive enzyme processing steps that are used in enzyme manufacturing. Implementing inhouse enzyme producing is expected to significantly reduce the cost of enzymes and biofuel processing cost.